2019
DOI: 10.18844/ijntss.v3i1.3815
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Microsoft IoT, machine learning in a large-scale power meter reading

Abstract: Due to fast technological progress in the power engineering field, the need of new information/communication technologies is more and more underlined. e-Learning has become a viable alternative to traditional teaching/learning techniques, adopted especially due to the advantages offered by the possibility of continuous training. This paper presents a Microsoft internet of things platform for a very large-scale smart power meter reading, used not only for training operative staff of the distribution network ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The least researched areas are Anatomy morphology (1), Area studies (1), Arts, humanities and other topics (1), Biochemistry molecular biology (1), Cell biology (1), Cultural studies (1), Dentistry oral surgery medicine (1 ), Development studies (1), General internal medicine (1), Genetics heredity (1), Geography (1), Instruments instrumentation (1), Materials science (1), Medical informatics (1), Neurosciences Neurology (1), Public environmental occupational health (1), Robotics (1), Social issues (1), Sport sciences (1) and Urban studies (1). Important research focuses on the importance of teamwork in education [26] [28] [29] [30]. For this reason, it can be said that the studies in this field are high.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The least researched areas are Anatomy morphology (1), Area studies (1), Arts, humanities and other topics (1), Biochemistry molecular biology (1), Cell biology (1), Cultural studies (1), Dentistry oral surgery medicine (1 ), Development studies (1), General internal medicine (1), Genetics heredity (1), Geography (1), Instruments instrumentation (1), Materials science (1), Medical informatics (1), Neurosciences Neurology (1), Public environmental occupational health (1), Robotics (1), Social issues (1), Sport sciences (1) and Urban studies (1). Important research focuses on the importance of teamwork in education [26] [28] [29] [30]. For this reason, it can be said that the studies in this field are high.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
“…Meeting abstracts 1 When we look at the distribution of the studies with regard to the place of computer in learning and teaching, which is among the studies in the Web of Science database categories, we can see that the most field of study is education and training research (172). Again, according to the fields of study, we concluded that studies were conducted in the fields of Computer science interdisciplinary applications (47), Education scientific disciplines (35), Computer science information systems (30) and Computer science theory methods (29). Among these fields, it is seen that Educational psychology (3) is the least field of study.…”
Section: Book Chaptermentioning
confidence: 99%
“…Especially, the development of computer and Internet technologies has made the use of information technologies indispensable in educational environments (Al Rub, 2015). It is known that the use of information technology supports, enriches and facilitates education (Pascu, Simo, & Vernica, 2019;Pinpathomrat, 2017). In addition, students are provided with the opportunity to learn according to their own abilities and speed with individualised education materials.…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
“…For successful business interaction among mother, multinational corporations, and even sister companies on the international scale, the use of English becomes a mass demand to achieve their various economic activities like production, import, and export of merchandise and services within the international trade, advertising for goods, writing emails for customers, complaint or application As for education, several investigations have been conducted on the use of E-learning to promote language learning. Scholars have reported different advantages of being considered a flexible approach that centers on the learners, allows for a more collaborative environment, facilitates communication between the teacher and the students, develops relationships, and sustains learning (Pascu, Simo & Vernica, 2019). The teacher is seen to be a medium enabling them to use different kinds of computer operating systems for the sake of learning and developing their autonomous ability (Arkorful & Abaidoo, 2014;Liaw & Hung, 2003;Twigg, 2002).…”
Section: Business Englishmentioning
confidence: 99%